The Tension Between Cognitive and Regulatory Flexibility and Their Associations With Current and Lifetime PTSD Symptoms - Haim-Nachum, Shilat; Levy-Gigi, Einat (Frontiers in Psychology, 2021)
In recent years, researchers have tried to unpack the meaning of the term flexibility and test how different constructs of flexibility are associated with various psychopathologies. For example, it is apparent that high levels of flexibility allow individuals to adaptively cope and avoid psychopathology following traumatic events, but the precise nature of this flexibility is ambiguous. In this study we focus on two central constructs: cognitive flexibility – the ability to recognize and implement possible responses to a situation– and regulatory flexibility – the ability to modulate emotional expression and experience across situations. We aim to explore the connection between cognitive and regulatory flexibility and evaluate their relative effect on PTSD symptoms. Trauma-exposed college students (N = 109, M age = 25.31, SD = 4.59) were assessed for cognitive and regulatory flexibility and current and lifetime PTSD symptoms. We predicted and found a relatively weak, yet significant, overlap between participants’ cognitive and regulatory flexibility. Importantly, while both cognitive and regulatory flexibility were associated with lifetime PTSD symptoms, only cognitive flexibility was associated with current PTSD symptoms. The findings illuminate the possible value of differentiating between constructs of flexibility in predicting short and long-term effects of traumatic exposure and may pave the ground for developing personalized intervention methods.